2010
DOI: 10.1364/oe.18.008540
|View full text |Cite
|
Sign up to set email alerts
|

50W CW visible laser source at 589nm obtained via frequency doubling of three coherently combined narrow-band Raman fibre amplifiers

Abstract: We demonstrate the cascaded coherent collinear combination of a seed-split triplet of 1178nm high-power narrow-band (sub-1.5MHz) SBS-suppressed CW Raman fibre amplifiers via nested free-space constructive quasi-Mach-Zehnder interferometry, after analysing the combination of the first two amplifiers in detail. Near-unity combination and cascaded-combination efficiencies are obtained at all power levels up to a maximum P(1178) > 60W. Frequency doubling of this cascaded-combined output in an external resonant cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(60 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…Noncritical phase matching is beneficial because it avoids a walk-off angle between the fundamental and harmonic waves, which tends to distort the harmonic beam shape [14] and limits the interaction length. Furthermore, several publications have reported that, at the employed intensity levels, LBO did not show the above-mentioned performance degradations (e.g., [15,16]). As we did not know if this holds for higher intensities, we intended to mitigate such problems in advance by use of a long crystal and by designing a considerably bigger waist inside the crystal than that which corresponded to maximum single-pass conversion efficiency (also known as Boyd-Kleinman focusing) [17].…”
mentioning
confidence: 95%
“…Noncritical phase matching is beneficial because it avoids a walk-off angle between the fundamental and harmonic waves, which tends to distort the harmonic beam shape [14] and limits the interaction length. Furthermore, several publications have reported that, at the employed intensity levels, LBO did not show the above-mentioned performance degradations (e.g., [15,16]). As we did not know if this holds for higher intensities, we intended to mitigate such problems in advance by use of a long crystal and by designing a considerably bigger waist inside the crystal than that which corresponded to maximum single-pass conversion efficiency (also known as Boyd-Kleinman focusing) [17].…”
mentioning
confidence: 95%
“…For example, output power of 50W is demonstrated with sum-frequency mixing of injection-locked Nd:YAG continuous-wave (CW) lasers [3]. The other is frequency doubling of 1178nm CW Raman fiber amplifiers and output power of 50W is achieved [4].…”
Section: Abstract-sum-frequency Generation; Yellow Laser; Solid-statementioning
confidence: 99%
“…For example, output power of 50W is demonstrated with sum-frequency mixing of injection-locked Nd:YAG continuous-wave (CW) lasers [3]. The other is frequency doubling of 1178nm CW Raman fiber amplifiers and output power of 50W is achieved [4].In this letter, we have developed a high beam quality and narrow linewidth yellow beam at 589nm by extra-cavity sumfrequency mixing 1064 and 1319 nm radiations of quasicontinuous-wave (QCW) diode-pumped Nd:YAG lasers in a LBO crystal. The 1064 and 1319nm lasers are generated by means of a diode-pumped Nd:YAG master-oscillator poweramplifier (MOPA) system.…”
mentioning
confidence: 99%
“…A bow-tie external resonant cavity incorporating an LBO nonlinear optical crystal is used for generating the second harmonic of the fiber laser. The LBO crystal is type-I noncritically phase matched, which avoids a walk-off effect between the fundamental and harmonic waves [19,20] . A 33.2 W green laser at 532 nm is generated with a 45 W incident fundamental laser.…”
mentioning
confidence: 99%